2014
DOI: 10.3390/molecules19068414
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, DFT Studies and Evaluation of the Antioxidant Activity of 3,4-Dimethoxybenzenamine Schiff Bases

Abstract: Schiff bases of 3,4-dimethoxybenzenamine 1 – 25 were synthesized and evaluated for their antioxidant activity. All the synthesized compounds were characterized by various spectroscopic techniques. In addition, the characterizations of compounds 13 , 15 and 16 were supported by crystal X-ray determinations and their geometrical parameters were compared with theoretical DFT calculations at the B3LYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 51 publications
(56 reference statements)
2
18
0
Order By: Relevance
“…The (E)-4-((6-chloro-2-oxoindolin-3-ylidene)methyl)benzohydrazide was treated with different acetophenones and aryl aldehydes in the presence of acetic acid to give desired products (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Scheme-2. …”
Section: Scheme-1mentioning
confidence: 99%
See 1 more Smart Citation
“…The (E)-4-((6-chloro-2-oxoindolin-3-ylidene)methyl)benzohydrazide was treated with different acetophenones and aryl aldehydes in the presence of acetic acid to give desired products (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Scheme-2. …”
Section: Scheme-1mentioning
confidence: 99%
“…Benzohydrazones were recently reported to possess diuretic [19], antioxidant [20][21][22][23], antiglycation [24][25][26] α-glucosidase [27] and antileishmanial [28] activities.…”
mentioning
confidence: 99%
“…Benzohydrazones having heterocyclic rings were reported to have antiglycation, anticonvulsant, Phosphodiesterase-1 inhibitors, antiproliferative, antifungal and anti-HIV activities (Kabak et al, 1999;Ku¨c¸u¨kgu¨zel et al, 2004;Khan et al, 2014a;Jamil et al, 2015;Pandeya et al, 1999). Several benzohydrazones reported interesting bioactivities, such as antifungal, anticonvulsant, anti-inflammatory, antibacterial, antimalarial, antiplatelets, analgesic, antituberculosis, antioxidant (Loncle et al, 2004;Ku¨c¸u¨kgu¨zel et al, 2003;Todeschini et al, 1998;Melnyk et al, 2006;Lima et al, 2000;Cunha et al, 2003;Kaymakc¸ıog˘lu et al, 2006;Aziz et al, 2014), antileishmanial, insecticidal, immunoconjugates, antimycobacterial, adriamycin proteinase inhibition and activity against protozoan parasite (Sawada et al, 2003;Taha et al, 2013;Ku¨c¸u¨kgu¨zel and Rollas, 2002;Greenfield et al, 1990;Caffery et al, 2002). Other benzohydrazone derivatives have reported b-glucuronidase ) and aglucosidase inhibition activity .…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, imidazole moiety is also considered significant for antiglycation activity as it was found that, free amino group of imidazole ring will competes with amine side groups of proteins in the presence of reactive dicarbonyl compounds (Brownson and Hipkiss, 2000). Benzohydrazides are reported to possess a broad variety of biological activities such as antiglycation (Khan et al, 2013a, b andKhan et al, 2015;Jamil et al, 2015), antioxidant (Aziz et al, 2014;Khan et al, 2012), antileishmanial , antibacterial (Imran et al, 2014), b-glucuronidase , urease and c) and a-glucosidase (Taha et al, 2015f).…”
Section: Introductionmentioning
confidence: 97%